How to motivate the rich: a research on Confucian economic ethics - Ng, Khai Boon (Nanyang Technological University, 2025)
This thesis explores the application of Confucian morality to political economy. For Confucianism, ethical considerations are essential in guiding the design and reform of political institutions and policies. This thesis focuses on moral considerations a government should heed in guiding economic activities. It aims to shed light on the scope of morality by investigating the historical record of the Shihuozhi, combining with textual analyses of other dominant Confucian texts. It suggests economic productivity is the main concern of economic development. However, economic actors are not always motivated to being productive, especially when their actions have caused social and economic inequalities. To motivate economic actors, the study found that there is a narrower scope of morality which is a preparation for one to become morally cultivated with de (virtue). For Confucianism, a normative arrangement is morally better when the agents are more motivated to act according to it. It relies on the agents’ sustainability of external act to monitor if they stay on the ethical path. When there are myriad of reasons that motivate a person as well as reasons that impede a person from acting, Confucianism requires the government to provide the condition in which there is no identifiable reason for the agents not to act according to the prescribed directions of the government. This study considers that the ethics of interest should be combined with the ethics of recognition to motivate the people towards altruistic actions that benefitting the people for achieving collective prosperity.